The Nrf2/Keap1/ARE Pathway and Oxidative Stress as a Therapeutic Target in Type II Diabetes Mellitus. (20th August 2017) - David, Joshua A.; Rifkin, William J.; Rabbani, Piul S.; Ceradini, Daniel J.
Abstract : Despite improvements in awareness and treatment of type II diabetes mellitus (TIIDM), this disease remains a major source of morbidity and mortality worldwide, and prevalence continues to rise. Oxidative damage caused by free radicals has long been known to contribute to the pathogenesis and progression of TIIDM and its complications. Only recently, however, has the role of the Nrf2/Keap1/ARE master antioxidant pathway in diabetic dysfunction begun to be elucidated. There is accumulating evidence that this pathway is implicated in diabetic damage to the pancreas, heart, and skin, among other cell types and tissues. Animal studies and clinical trials have shown promising results suggesting that activation of this pathway can delay or reverse some of these impairments in TIIDM. In this review, we outline the role of oxidative damage and the Nrf2/Keap1/ARE pathway in TIIDM, focusing on current and future efforts to utilize this relationship as a therapeutic target for prevention, prognosis, and treatment of TIID.